MODEL SISTEM DINAMIS UNTUK ESTIMASI PENCEMARAN UDARA DARI EMISI KENDARAAN BERMOTOR DI JAKARTA - Nuraini Soleiman; Rudy C Tarumingkeng (LPPM Universitas Terbuka, 2008)
Air pollution from vehicle emission becomes a major problem in urban areas, including Jakarta, Indonesia. This vehicle emission worsening ambient air concentration because of increasingly use of diesel engine for urban transportation, which exhaust particulate matter. This pollutan pose adverse health effect especially resparatory problems and premature mortality. This paper presents a model for estimating the level of pollution and the impact of that pollution on human health. An air quality model is developed using Gaussian model for urban area and the social-economic impact are estimated using Dose Response function. Simulation of the model shows a dynamic model is a powerfull tool for estimating the pollution level and the impact of the pollution. The result of the simulation can be used as basic information for decision makers to design some environmental policies for reducing the pollution level from vehicles emission.